1989
DOI: 10.1159/000185651
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Uremic Toxins – Guanidino Compounds and Creatinine – on Proliferation of HL60 and K562 Cell Lines

Abstract: Growth of the promyelocytic cell line HL60 and the erythroleukemia cell line K562 is inhibited by ‘uremic toxins’: creatinine, guanidino propionic acid and guanidino succinic acid in a concentration range similar to that of uremic sera. Among the tested compounds, creatinine exhibits the strongest and most dose-dependent inhibitory effect on both kinds of cells. These results provide a better understanding of the mechanism involved in the anemia of uremic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…(p<0.02; table 2). Together with the data that HL-60 cell differentiation is associated with suppression of cell prolif eration, the finding that cell numbers after 5 days of treat ment were similar in the control and uremic serum-treated cells indicates that proliferation of HL-60 cells was sup pressed by uremic serum as reported previously [18].…”
Section: Effect O F Normal or Uremic Serum On 125-(oh):dr In Duced Dsupporting
confidence: 87%
See 2 more Smart Citations
“…(p<0.02; table 2). Together with the data that HL-60 cell differentiation is associated with suppression of cell prolif eration, the finding that cell numbers after 5 days of treat ment were similar in the control and uremic serum-treated cells indicates that proliferation of HL-60 cells was sup pressed by uremic serum as reported previously [18].…”
Section: Effect O F Normal or Uremic Serum On 125-(oh):dr In Duced Dsupporting
confidence: 87%
“…The results obtained from a mixing study strongly suggested the occurrence of sub stance^) which inhibited the action of l,25-(OH)2D3 on these cells. Also, a significant suppression of cell prolifera tion was observed with uremic serum treatment as pre viously described [18]. However, as HL-60 cell proliferation is not coupled to its differentiation as we [3,22] and others [29,30] have previously demonstrated, the proliferationsuppressive effect of uremic serum could be neglected in assessing the effect of I,25-(OH)2D3 on cell differentiation.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In contrast, Nathan et al [25] reported that creatinine, guanidinopropionic acid, and guanidinosuccinic acid inhibit the growth of HL-60 cells and of the erythroleukemia cell line K562. It is of note, however, that these authors applied concentrations up to 200 times higher than those used in the present study; in addition, proliferation was determined by counting the colony formation on tissue culture dishes, which is a less accurate method compared to the flow cytometric method used in this study.…”
Section: Discussionmentioning
confidence: 91%
“…Hirayama et al [24] described that a mixture of guanidino compounds suppresses the production of superoxide by normal isolated neutrophils. Furthermore, guanidino compounds such as guanidinosuccinic acid, creatinine, and guanidinopropionic acid, have been shown to inhibit HL-60 and K562 cell line proliferation [25]. Finally, Autore et al [26] reported that methylguanidine downregulates the tumor necrosis factor-a (TNF-a) release by activated macrophages, but other guanidino compounds were not evaluated.…”
mentioning
confidence: 99%